Information and communications technologies in postgraduate medical education - Orellano-Tuesta, Carlos Alberto (2019)
Digital education in postgraduate medicine programs offers tools that fit with the characteristics of the currentprofessional who seeks alternatives to continue acquiring knowledge. The aim of this paper is to address the conditions for its effectiveness and point out certain applications reported in the international literature. Also, usages in Peru are mentioned, including the experience in the medical residency of the Peruvian University Cayetano Heredia.